Propiedades nucleares de los fenómenos mentales según Searle: intencionalidad, subjetividad, semanticidad* - Álvarez Rodríguez, Asunción (Revista de Filosofía, 2002)
This essay aims to be a characterization of the Searlean conception of mental phenomena. For Searle, the mental nature of brain processes is determined by their capacity to become conscious. Thus, what Searle takes to be the main features of consciousness – subjectivity and intentionality – are expounded, as well as their interaction and their inscription within the larger framework of the semanticity of human thought